Making a Commitment to EBLIP: The Role of Library Leadership - Suzanne F Grefsheim; Jocelyn A Rankin; Susan C Whitmore (Evidence Based Library and Information Practice, 2007)
Purpose - The role of library management and administration is pivotal to successful adoption of evidence-based practice by library practitioners. As part of its long-standing commitment to a learning organization, the leadership team of the biomedical research library serving the National Institutes of Health in Bethesda, MD, USA planned and implemented a systematic approach to fostering EBLIP practice.